2008
DOI: 10.1017/s1047951108002175
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric cardiac assistance in developing and transitional countries: the impact of a fourteen year effort

Abstract: Background: Paediatric cardiac services are poorly developed or totally absent in underdeveloped countries. Institutions, foundations and interested individuals in those nations in which sophisticated paediatric cardiac surgery is practised have the ability to alleviate this problem by sponsoring paediatric cardio-surgical missions to provide care, and train local caregivers in developing, transitional, and third world countries. The ultimate benefit of such a programme is to improve the surgical abilities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Novick et al . showed that a visiting surgical team can significantly improve local care, as indicated by the increased number and complexity of cases in the visited institutions . This indicates that the development of independent and sustainable programs within developing countries should be the ultimate goal of external interventions and that long‐term commitment of both the visiting team and the local recipient institution is important.…”
Section: Discussionmentioning
confidence: 98%
“…Novick et al . showed that a visiting surgical team can significantly improve local care, as indicated by the increased number and complexity of cases in the visited institutions . This indicates that the development of independent and sustainable programs within developing countries should be the ultimate goal of external interventions and that long‐term commitment of both the visiting team and the local recipient institution is important.…”
Section: Discussionmentioning
confidence: 98%
“…Certainly, there is evidence in the literature that various organisations have helped to establish sustainable programmes using a system of repeated surgical trips with an emphasis on teaching. 8,9 Future work could include interview or focus-group studies of local providers to learn their perceptions of the relationships. It could also be informative to do similar work focussing on other forms of humanitarian assistance, such as the effect on or perception of local providers when patients are either sent out for surgery, or when a permanent local institute is established totally or partly staffed by foreigners.…”
Section: Limitationsmentioning
confidence: 99%
“…There is a growing consensus about the need to work together to build regional centres which themselves can become a resource to surrounding areas and countries through satellite outreaches. (84,85,86,87) Such regional "surgical hubs" could form training and resource bases for surrounding countries, with international aid coordinated at one centre rather than being diluted through multiple small efforts. is directed toward first-world needs for both pharmaceuticals and technology.…”
Section: Preventionmentioning
confidence: 99%
“…(87) A degree of education of the local community and recruitment of political leadership is important.…”
Section: Build Local Infrastructure Through Teamsmentioning
confidence: 99%